2018
DOI: 10.1016/j.sjbs.2017.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous 6-BA and NAA on growth and contents of medicinal ingredient of Phellodendron chinense seedlings

Abstract: Using seedlings as material, and treated with different concentrations of exogenous 6-Benzylaminopurine (6-BA) and α-naphthyacetic acid (NAA), then observed the growth status. Furthermore, we detected the contents of chlorophyll and soluble sugar, the activities of antioxidases by spectrophotometry, and determined the contents of secondary metabolite by high performance liquid chromatograph. The results showed that different concentrations of exogenous 6-BA increases the fresh weights and plant heights of seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…When leaves of O. Fragrance were under high temperature stress, ADH gene expression would be increased because of the resistance response mechanism activation in order to avoid from heat damage. Many researches about functional components in the leaves, flowers (Ge et al, 2018a and2018b), barks (Ge et al, 2017a and, stems (Ge et al, 2017c and2017d), roots (Ge et al, 2017e;, fruits (Jiang et al, 2018a and2018b), timbers (Peng et al, 2017a and and byproducts (Liu et al, 2017;Xie et al, 2018) of plants showed that they contain many bioactive components (Peng et al, 2016;He et al, 2017;Cheng et al, 2017;Yang et al, 2017;Qin et al, 2017;Xu et al, 2018;Wang et al, 2018). This result was consistent with the resistance response function of ADH (Strommer et al, 2011).…”
Section: Discussionsupporting
confidence: 69%
“…When leaves of O. Fragrance were under high temperature stress, ADH gene expression would be increased because of the resistance response mechanism activation in order to avoid from heat damage. Many researches about functional components in the leaves, flowers (Ge et al, 2018a and2018b), barks (Ge et al, 2017a and, stems (Ge et al, 2017c and2017d), roots (Ge et al, 2017e;, fruits (Jiang et al, 2018a and2018b), timbers (Peng et al, 2017a and and byproducts (Liu et al, 2017;Xie et al, 2018) of plants showed that they contain many bioactive components (Peng et al, 2016;He et al, 2017;Cheng et al, 2017;Yang et al, 2017;Qin et al, 2017;Xu et al, 2018;Wang et al, 2018). This result was consistent with the resistance response function of ADH (Strommer et al, 2011).…”
Section: Discussionsupporting
confidence: 69%
“…Plant hormones play critical roles in plant growth and differentiation as well as the accumulation of medicinal ingredients (Marı´n et al 2001;Liu et al 2018;He et al 2018). Plant hormones increase the expression of related enzyme genes in the secondary metabolite synthesis pathway, thereby increasing enzyme activity and ultimately increasing the accumulation of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Tetradecanal (0.41%) is an edible spice that is used to mix peach, fat and milk flavors. The degradation products of Neophytadiene (1.34%) have an important contribution to tobacco aroma (He et al, 2018). 2-Propanone, 1-(4-hydroxy-3-methoxyphenyl) - (1.86%) can release volatile aromatic compounds, which contribute to the aroma of barrel wine (Truong et al, 2017).…”
Section: Resultsmentioning
confidence: 99%